Implementation of Islamic religious learning education to increase intra-religious tolerance behavior - Mukhlis Adi Nugraha (IAIN Salatiga, 2017)
This study aims to determine the implementation of learning PAI to improve the behavior of intra-religious tolerance. This type of research is qualitative, using observation data collection techniques, interviews, and documentation. Implementation of learning PAI in SMK Karya Nugraha Boyolali has been using curriculum 2013. While SMK Muhammadiyah 04 Boyolali still not fully use the curriculum 2013. If the PAI in SMK Karya Nugraha Boyolali taught in one subject, unlike the case in SMK Muhammadiyah 04 Boyolali, subjects PAI taught separately. In addition, there are differences from Strategy, Method, Learning Resources, Media, Material, and Evaluation of Learning. Factors supporting intra-religious tolerance in SMK Karya Nugraha Boyolali is the teacher explains the various streams, without vilifying; while for the inhibiting factor is the diverse background of student organizations. Factors supporting intra-religious tolerance in SMK Muhammadiyah 04 Boyolali an open understanding, the inhibiting factor is the lack of understanding of religious knowledge related to khilafiyah which raises the most correct personal views. Efforts to increase intra-religious tolerance in SMK Karya Nugraha by conveying various kinds of schools, schools within Islam. For SMK Muhammadiyah 04 Boyolali emphasize on the explanation of the arguments khilafiyah.